(R)ewolucja w klasie szkolnej. O potrzebie (re)organizacji przestrzeni edukacyjnej - Grześko-Nyczka, Marta (Tomorrow's school? Tradition and (r)evolutions in education, 2023)
The contemporary world is characterized by dynamic changes and progress in almost every area of life, while education, which is the engine for all development, is still carried out in the Prussian model, with a history of two centuries. The necessity to undertake activities aiming at adapting education to the requirements of the 21st century reality seems indisputable. The article attempts to show how the reorganization of classroom space can mark the beginning of revolutionary changes in the functioning of primary schools. It highlights the need to transform the ‘old’ one-way teaching model into a „new” approach based on learning from each other. This is going to be achieved through the change of desk arrangement, which, in a way, forces the need to remodel both the role of the teacher and the student. An appropriate organization of classroom space allows teachers to implement the methods which break with the traditional pattern of knowledge transmission and enable the development of competences that are important today. The teacher then becomes the organizer of a learning process, and the students are its important subjecs – active participants. The article also contains a list of good teaching practices, which can be implemented in a modern public school in order to minimize the importance of frontal teaching.